93.5k views
0 votes
If f(x)=x-6 and g(x)=x1/2(x+3), find g(x) times f(x)

User Jwildsmith
by
5.4k points

1 Answer

3 votes
To solve this problem you must apply the proccedure shown below:
1. You have the following functions given in the problem above:

f(x)=x-6 and
g(x)=x1/2(x+3)=x(x+3)/2
2. You have that g(x) times f(x) can be written as g(x)*f(x). Therefore, you must multiply f(x) * g(x), as following:

g(x)*f(x)=(x-6)*x(x+3)/2
3. Applying the distributive property, you have:

g(x)*f(x)=( x^(3) + 3x^2 - 6x^(2) -18x)/2

g(x)*f(x)=(x^(3) - 3x^(2) -18x)/2
The answer is:
</strong>g(x)*f(x)=(x^(3) - 3x^(2)&nbsp;-18x)/2<strong>
User Unwired
by
5.8k points